Implementasi Analisis Teknikal dan Fundamental serta STP untuk Ketepatan Open Posisi pada Klien Pemula di Perusahaan Berjangka - Fikry Adie Pratama; Wilma Cordelia Izaak (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
In understanding the basics of technical and fundamental analysis as a starting point before making trading decisions, through a simple and easy-to-understand approach, novice clients are introduced to technical analysis by looking at candlestick charts, recognizing the direction of market trends, and using technical indicators to assess the strength of price movements. Fundamental analysis, on the other hand, is explained as a way to understand the global economic situation, world political conditions, and international policies that affect the market, although it is not always the main basis for direct transactions. The participatory qualitative method used in the service with an educational approach based on interactive discussions and practical simulations. The main target audience was novice clients who were new to trading. Education is delivered in a gradual and focused manner, with the application of the STP (Segmenting, Targeting, Positioning) concept to help participants design trading strategies that suit the character and needs of novice clients. With this method, it is expected that novice clients can make trading decisions more wisely, measurably, and not only based on speculation.